Haptoglobin phenotype, pre‐eclampsia, and response to supplementation with vitamins C and E in pregnant women with type‐1 diabetes. Issue 10 (30th May 2013) - Weissgerber, TL; Gandley, RE; Roberts, JM; Patterson, CC; Holmes, VA; Young, IS; McCance, DR; ,
<x xml:space="preserve">Abstract</x> Objective The phenotype of the antioxidant and pro‐angiogenic protein haptoglobin (Hp) predicts cardiovascular disease risk and treatment response to antioxidant vitamins in individuals with diabetes. Our objective was to determine whether Hp phenotype influences pre‐eclampsia risk, or the efficacy of vitamins C and E in preventing pre‐eclampsia, in women with type‐1 diabetes. Design This is a secondary analysis of a randomised controlled trial in which women with diabetes received daily vitamins C and E, or placebo, from 8 to 22 weeks of gestation until delivery. Setting Twenty‐five antenatal metabolic clinics across the UK (in north‐west England, Scotland, and Northern Ireland). Population Pregnant women with type‐1 diabetes. Methods Hp phenotype was determined in white women who completed the study and had plasma samples available (n = 685). Main outcome measure Pre‐eclampsia. Results Compared with Hp 2‐1, Hp 1‐1 (OR 0.59, 95% CI 0.30–1.16) and Hp 2‐2 (OR 0.93, 95% CI 0.60–1.45) were not associated with significantly decreased pre‐eclampsia risk after adjusting for treatment group and HbA1c at randomisation. Our study was not powered to detect an interaction between Hp phenotype and treatment response; however, our preliminary analysis suggests that vitamins C and E did not prevent pre‐eclampsia in women of any Hp phenotype (Hp 1‐1, OR 0.77, 95% CI 0.22–2.71; Hp 2‐1, OR 0.81, 95% CI 0.46–1.43; Hp 2‐2, 0.67, 95% CI 0.34–1.33), after adjusting for HbA1c at randomisation. Conclusions The Hp phenotype did not significantly affect pre‐eclampsia risk in women with type‐1 diabetes.